The Importance of The Spiritual Quotient in Society Life - Putu Yulia Angga Dewi; Kadek Hengki Primayana (Purwadita : Jurnal Agama dan Budaya, 2023)
Spiritual intelligence is closely related to intellectual intelligence and emotional intelligence. In line with what was conveyed by Zohar and Marshall, spiritual intelligence is the foundation needed to function intellectually and emotionally effectively. Intellectual intelligence is the ability of the human soul to carry out logical functions properly, or what we call rational. The importance of paying attention to spiritual intelligence in our life's journey is because spiritual intelligence has many benefits. The benefits of spiritual intelligence include being able to distinguish between right and wrong, growing the development of the human brain, and achieving self-development